Medicinal Mushrooms, Probiotics and Combination of Natural Compounds in the Management of HPV: A Comparative Look at Viral Clearance and Lesion Resolution - Giuseppina Porcaro; Marco Calcagno; Andrea Tinelli (Viruses)
Despite the fact that human papillomavirus (HPV) infections are common, there are currently no proven treatment approaches for persistent infections. A promising strategy to promote HPV clearance and the regression of caused lesions is dietary supplementation with natural compounds. This review evaluates available supplement formulations proposed in HPV care, focusing on combinations of epigallocatechin gallate (EGCG), folic acid (FA), vitamin B12 (B12), and hyaluronic acid (HA), as well as medicinal mushrooms and probiotics. The combination of EGCG, FA, B12, and HA is supported by the most consistent evidence, which shows a high rate of HPV clearance and lesion resolution across several clinical investigations. Medicinal mushrooms and probiotics have also shown some evidence of beneficial effects, although the diverse designs of the reported clinical studies may limit the observed findings. Overall, natural molecule-based supplements showed promising safety and efficacy profiles in the management of HPV persistent infection, supporting their clinical use. Of course, further investigations through well-designed, large-scale, randomized controlled trials will be necessary to provide strong support.